Assessment of clinical prognosis in autoimmune encephalitis: Girona score - Álvarez Bravo, Gary; Guglielmini, Giuseppe; Quiroga Varela, Ana; Boix Lago, Almudena; Gifreu Fraixinó, Ariadna; Urso, Daniele; Logroscino, Giancarlo; Ramió-Torrentà, Lluís (Frontiers in Psychiatry, 2025)
BackgroundThe assessment of clinical prognosis in autoimmune encephalitis: Girona (ACPE-Gi) score is a scale for evaluating the severity in the acute phase of autoimmune encephalitis (AE) and predicting the risk of disability at 3 months, measured by modified Rankin scale (mRS).MethodsPatients were strictly diagnosed with AE according to the current criteria between 1 January 2009 to 31 March 2023 at the University Hospital Dr. Josep Trueta of Girona, Catalonia, Spain. ACPE-Gi score included 14 items, and every item was scored from 0 to 3, depending on their severity with a sum ranging from 0 to 41.ResultsACPE-Gi score measured the severity in the acute phase and grouped the patients into three groups: mild (<8; 32%), moderate (8 to 15; 60%), and severe (>15; 8%). We found that the third group had a higher risk of disability compared with the first group (p = 0.035). We identified that the mean initial score was significantly higher in the group of patients who had higher mRS at 3 months compared to that in the group of patients who had a mild to moderate disability level (mRS ≤ 2) at 3 months (p = 0.023). In addition, autonomic symptoms and mental status impairment demonstrated to be independent risk factors to predict disability (p < 0.05).ConclusionsThe ACPE-Gi score seems to be a reliable scale for comprehensively evaluating the severity of AE in the acute phase and predicting the risk of disability at 3 months. Dysautonomia and altered mental status predict a poorer prognosis in patients with AE.